Association between Knowledge, Attitudes, and Behavior of Household Hazardous Waste Management in That Sub-district, Warinchamrab Ubon Ratchathani - จันทร์ศิริ, สุภาณี; ใจขาน, สิทธิชัย; อันถาวรพงศ์, ณัฐภัทร; ทองดำรงธรรม, สมเจตน์; ศุภสุข, ดลภัทร (Journal of Health Science of Thailand, 2022)
The objectives of this study were to study the level of knowledge, attitudes, and behavior of hazardous waste management and the association between knowledge, attitudes, and behavior of household hazardous waste management. It was conducted as a cross-sectional descriptive study in That Sub-district, Warinchamrab Ubon Ratchathani. Data were collected by using questionnaires with a total of 220 people (household hazardous waste manager) by simple random sampling. Data analysis techniques were a descriptive statistic, i.e., frequencies, percentage, mean and standard deviation. It was found that the overall waste management knowledge of households was at a highest level (55.5%), the solid waste management attitudes were at highest level (94.1%), and the solid waste management behavior was moderate level (61.8%). An statistically significant association between behavior of household hazardous waste management was observed (p<0.05). This study shows that people with undesirable behavior such as throwing deteriorated drugs or cosmetics, old batteries, electronic equipment waste, or containers of pesticides/chemicals/volatile substances; and not disposing hazardous waste at domestic collection points. That sub-district municipality should organize training on hazardous wastes management. and promote awareness, attitude, and understanding about hazardous waste disposing as well as the need for waste disposal at domestic hazardous waste collection points.